Application of quinoline derivatives in third-generation photovoltaics - Lewinska, Gabriela; Sanetra, Jerzy; Marszalek, Konstanty W. (Journal of materials science. Materials in electronics, 2021)
Among many chemical compounds synthesized for third-generation photovoltaic applications, quinoline derivatives have recently gained popularity. This work reviews the latest developments in the quinoline derivatives (metal complexes) for applications in the photovoltaic cells. Their properties for photovoltaic applications are detailed: absorption spectra, energy levels, and other achievements presented by the authors. We have also outlined various methods for testing the compounds for application. Finally, we present the implementation of quinoline derivatives in photovoltaic cells. Their architecture and design are described, and also, the performance for polymer solar cells and dye-synthesized solar cells was highlighted. We have described their performance and characteristics. We have also pointed out other, non-photovoltaic applications for quinoline derivatives. It has been demonstrated and described that quinoline derivatives are good materials for the emission layer of organic light-emitting diodes (OLEDs) and are also used in transistors. The compounds are also being considered as materials for biomedical applications.